Impact of Metabolic Syndrome on the Progression of Coronary Artery Disease: An Observational Cohort Study (Medical Forum Monthly, 2024)
Objective: The objective of study was to evaluate the impact of MetS on the progression of CAD across diverse patient populations.Study Design: An observational cohort studyPlace and Duration of Study: This study was conducted at the department of Medicine and Cardiology at Nishtar II Medical University and Hospital, Multan, from September 2023 to August 2024.Methods: Total 424 participants aged between 30 to 75 years diagnosed with MetS according to the International Diabetes Federation criteria. Clinical exams, structured interviews, and reviews of medical records were used to gather data. Important laboratory and anthropometric data were assessed at baseline and after 6, 12, 18, and 24 months of follow-up. Regression models were used in the statistical studies, which were carried out using SPSS version 26, to evaluate the connections between the components of the MetS and the advancement of CAD.Results: The results showed a significant positive correlation with the progression of CAD between waist circumference, systolic blood pressure, and fasting blood glucose levels (β = 0.15, p = 0.002; β = 0.18, p = 0.003; and β = 0.22, p = 0.001, respectively). Participants showed significant improvements in metabolic parameters during the 24-month follow-up period, including a drop in fasting blood glucose levels to 99.89 mg/dL and a reduction in waist circumference to 87.03 cm and systolic blood pressure to 123.87 mmHg. Furthermore, good improvements were seen in lipid profiles, demonstrating the beneficial effects of focused therapies on cardiovascular health.Conclusion: This study indicates how crucial MetS is in accelerating CAD development. It also emphasizes how crucial early preventive and sensible risk control are for reducing cardiovascular risk.